2013
DOI: 10.1371/journal.pone.0063031
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of Resistance Training and Aerobic Training versus Balance and Toning Exercises in Older Adults with Mild Cognitive Impairment

Abstract: BackgroundMild cognitive impairment (MCI) represents a critical window to intervene against dementia. Exercise training is a promising intervention strategy, but the efficiency (i.e., relationship of costs and consequences) of such types of training remains unknown. Thus, we estimated the incremental cost-effectiveness of resistance training or aerobic training compared with balance and tone exercises in terms of changes in executive cognitive function among senior women with probable MCI.MethodsEconomic evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 45 publications
0
47
0
2
Order By: Relevance
“…Baker et al 2010;Mirelman et al 2011;Davis et al 2013;Tabak et al 2013). Our research has demonstrated that in a cognitive-motor dual-task training program with 12 sessions, the dual-task training was only statistically more effective than the single-task training for the COPx with eyes closed.…”
Section: Discussionmentioning
confidence: 58%
“…Baker et al 2010;Mirelman et al 2011;Davis et al 2013;Tabak et al 2013). Our research has demonstrated that in a cognitive-motor dual-task training program with 12 sessions, the dual-task training was only statistically more effective than the single-task training for the COPx with eyes closed.…”
Section: Discussionmentioning
confidence: 58%
“…Aside from Makai et al [39] and Henderson et al [54], no other economic evaluation employing an ICECAP measure has to date produced an ICER with respect to the measure. This is likely to be due to the measure being new and unfamiliar to decision makers, so the evaluation team has used EQ-5D/ QALYs (as Henderson et al [54] do) or a clinical measure [55]. Of course, 15 years ago we did not have an explicit cost-effectiveness threshold for the QALY 9 ; something similar may come with time, however, it could be further complicated by the fact that the measure is broader than health so it may additionally be necessary to estimate the opportunity cost from a budget that is wider than the health budget.…”
Section: Outstanding Issuesmentioning
confidence: 99%
“…Table 1. A list of excluded studies [32,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] can be also found in Suppl. Table 2.…”
Section: Resultsmentioning
confidence: 99%